Fault-Tolerant UAV Data Acquisition Schemes - Alemayehu, Temesgen Seyoum; Kim, Jai Hoon; Yoon, Wonsik (Wireless Personal Communications, 2020)
Through the use of UAV, the functional lifetime of WSN can be elongated in exchange for higher data delivery latency as the UAV replaces the multi-hop communication among nodes during data acquisition. Due to the NP-hardness of the TSP whose computational complexity increases exponentially as an increment of number of nodes, heuristic algorithms, such as nearest neighbor heuristic TSP algorithm (NN), have been developed for reducing this data delivery latency in shortest possible time. In our previous research work we have published the directional NN algorithm directed to the next nearest node (DDNN) (Alemayehu and Kim in Wirel Pers Commun 95:3271–3285, 2017) which modifies the existing NN algorithm to gain a reduction in this data delivery latency. However, the DDNN algorithm does not consider the reliability of the system in case of node or link failures. To collect the sensing data rapidly and reliably, the DDNN algorithm should be able to react to node or link failures and manage the data transmissions effectively in the network. In this study, we propose an extension of the DDNN scheme, fault tolerable DDNN scheme for data gathering to gain a reduction in the data acquisition time with fault-tolerant capability. The performance analysis has demonstrated that our proposed algorithm tolerates fault in case of malfunctions of sensors due to node/link failures and improves the detection rate of the DDNN scheme up to 34.93% at the cost of a little bit distance.
Keywords: Data gathering; Detection rates; Fault-tolerant; Fault-tolerant capability; Multi hop communication; Nearest neighbors; Performance analysis; TSP algorithms; Data acquisition; Drone; Fault-tolerance; Monitoring; UAV; WSN